Evaluating the Effectiveness of Mobile Applications for ESP Instruction in Engineering Disciplines - Dr. Muhammad Ehtsham; Muhammad Inam (Dialogue Social Science Review (DSSR), 2025)
The use of mobile technology in the field of ESP is a new concept, particularly in third-world countries. The present research is conducted in an engineering college in which there are two sections of electrical engineering class: section “A”, called the experimental group, and section “B”, called the control group. The data, which is collected through FGD, Pre-test, Post-test, and questionnaires from the students, shows that all the ESP teachers and the learners believed that the integration of mobile technology in teaching and learning ESP is fruitful and motivated the students to learn a specific language for their commercial use. Abbreviations: ESP (English for Specific Purpose), FGD (Focus Group Discussion), ICT (Information and Communication Technologies)